2013
DOI: 10.1002/etc.2277
|View full text |Cite
|
Sign up to set email alerts
|

The use of tetragnathid spiders as bioindicators of metal exposure at a coal ASH spill site

Abstract: On 22 December 2008, a dike containing coal fly ash from the Tennessee Valley Authority Kingston Fossil Fuel Plant (TN, USA) failed, resulting in the largest coal ash spill in US history. The present study was designed to determine sediment metal concentrations at multiple site locations and to determine whether site-specific bioaccumulation of metals existed in tetragnathid spiders. Selenium and nickel were the only 2 metals to exceed the US Environmental Protection Agency sediment screening levels. Selenium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 34 publications
0
48
0
Order By: Relevance
“…Most of the ash remained within 1 km of the site and was removed from the river during the 5 yr following the spill; however, a substantial amount of ash still remains in the Emory River, with some being transported downstream into the Clinch River ( Figure 1) and even farther downstream into the Tennessee River. In addition, multiple studies were undertaken by other investigators on a variety of other aquatic and terrestrial receptors [2][3][4]. These studies were conducted by several investigators and covered the range of biological organization from biochemical to physiological to organs to population and community.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the ash remained within 1 km of the site and was removed from the river during the 5 yr following the spill; however, a substantial amount of ash still remains in the Emory River, with some being transported downstream into the Clinch River ( Figure 1) and even farther downstream into the Tennessee River. In addition, multiple studies were undertaken by other investigators on a variety of other aquatic and terrestrial receptors [2][3][4]. These studies were conducted by several investigators and covered the range of biological organization from biochemical to physiological to organs to population and community.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the Kingston spill showed similar results for raccoons, with no spatial pattern of metal concentrations observed (Souza et al 2013). However, multiple other studies have observed significant increases, mainly in selenium and arsenic concentrations, at ash-associated sites compared to references locations in fish (Otter et al 2012) and spiders (Otter et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…As unfortunate as the spill was, it provided an opportunity to directly study the impact of coal fly ash in a large lotic system where the amount of downstream transport of ash was also being investigated and monitored (TVA 2010b). Previous research on the Kingston spill has provided insight on the contaminants of concern from multiple perspectives including sediment biogeochemistry, metal speciation, and metal bioaccumulation across multiple organisms (Ruhl et al 2010;Bednar et al 2010;Ruhl et al 2009;Otter et al 2013;Deonarine et al 2013;Bartov et al 2012;Liu et al 2013;Beck et al 2013;Souza et al 2013). Otter et al (2012) showed elevated concentrations of arsenic and selenium in various tissues of multiple fish species at ash-associated sites compared to reference sites.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, 1 840 000 km of streams and rivers are under human fish consumption advisories for Hg contamination . Mercury is commonly introduced to lotic ecosystems by atmospheric deposition and watershed runoff , and Se may be introduced from point sources such as coal ash or from irrigation returns in landscapes with seleniferous soils .…”
Section: Introductionmentioning
confidence: 99%